Determining the Relationship Revaluation of Property, Plant and Equipment Company on Stock Prices and the Rate of Return on Stock on Indonesian Stock Exchange - Evinita , Lenny Leorina (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The purpose of this study was to determine the impact of revaluation of property, plant, and equipment on stock prices and the rate of return on stock in a manufacturing company. The manufacturing firms represented in the index LQ45 on the Indonesia Stock Exchange from January 2011 to December 2013 were included in the population. The data were examined using multiple regression and the descriptive approach. The information was acquired via data collecting, data processing, and statistical analysis from an annual financial report on the Indonesian stock exchange. The main objective of the financial statement is to provide information about the financial position, performance, and the changes in the company's financial position that will be useful for economic decision-making. The findings of this study indicate that: 1) There is a relationship between the financial asset classes of property, plant, and equipment at fair value with reliability, 2) Reporting of fixed asset property, plant, and equipment at fair value biased and unreliable especially for SE (The difference between the change in the value of assets) and PPNINC (the increase of the value of property, plant, equipment company in period t), and 3) The fair value can explain the explanatory power which is quite significant to the stock price, exceeds that can be presented with the historical cost. The conclusion drawn from the findings is that asset reporting at fair value did not exhibit a reliable quality. This resulted from a discrepancy in the reporting of a growth in the value of property, plant, and equipment in some quarters and an exaggerated increase in the value of firm assets in certain periods. Additionally, changes in the value of property investment, plant, and equipment were recorded together with investor assessments and carried a reliability value.